Challenges Faced By Female Employees Working In Hotels And Role Of Hr ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: Women are vital members of society who contribute significantly to the well- being of their families and  society at large. Objective: The objective of this paper was to study the invisible barriers as a challenge in the career  advancement for women in the hospitality industry and to seek the female worker’s views on work place grievances  within the hotel industry. Methodology: Quantitative research design was used to understand the challenges faced  by female employees working in the hotel. The items in the questionnaire included working women issues related key  parameters like sexual and mental harassment, promotion issues, family care issues, discrimination based on gender,  workplace discrimination and prejudices, work life balance issues etc. A questionnaire-based survey of female (60) hotel  workers in Kolkata was done. The data was collected using the personal contact approach. Results: The majority age  group that participated in the study was under 21 to 29 years. About 78.3 % respondent’s organization does not provide  with childcare facility, though 73.3 % respondent’s organization do provide with adequate maternity leave. Around 60 %  of the respondent’s promotion took longer than those of male colleagues in the similar rank, which focus light on gender  inequality. About 75 % women experienced biasness in their place of work based on gender. Gender discrimination  and biasness are still existential in the industry. The rate of work satisfaction, stood at 43.3 %. Conclusion: The result  explains that there are areas that are slowly changing for the betterment of women, there is still few barriers and  challenges that makes it difficult for a female employee in a hotel industry. Women representation at the senior level is  also proportionately very low compared to men. Conflict between work and family is a real juggling act for women which  may at times lead her to make a choice between career and home.
Keywords: Women; Wellbeing; Barrier; Challenges; Work Place